Development of ILeMBA to Improve Class V Student Learning Outcomes in Science and Technology Lesson Content in Tegal Regency Elementary Schools - Aimatul Zaqiyah; Elok Fariha Sari (Indonesia Approach Education, 2024)
In learning, to make it easier for students to understand the material, it is necessary to use media. This research aims to develop and test the feasibility, practicality, and effectiveness of ILeMBA in improving student learning outcomes in Natural and Social Sciences (IPAS) material on the structure of the earth's layers in class V elementary school. This type of research is Research & Development (R&D) with the Borg and Gall model which is limited to the eighth stage of this research. The research subjects involved 27 students (14 female students and 13 male students). The instruments used are expert validator sheets, needs questionnaires, responses, and test questions. The validation results from media experts reached 91% and 93% from material experts showed that the media was